Eco-litecrete : from waste to wealth - Khairunisa, Muthusamy; Fadzil, Mat Yahaya; Saffuan, Wan Ahmad; Mohamad, Hafizuddin; Mohd Hanafi, Hashim; Muhammad Nazrin Akmal, Ahmad Zawawi; Nur Azzimah, Zamri (2018)
Malaysian palm oil industry and coal industry generates huge amount of wastes causing environmental pollution. Oil palm shell (OPS), the solid waste from palm oil mill when disposed consumes large landfill area, pollutes the environment and requires huge cost for waste management. Fly ash from the coal industry when dumped at the landfill causes contamination of water, soil and underground aquifers resulting in imbalance ecosystem. ECO-LITECRETE is produced to solve industrial wastes problems to create a cleaner environment for healthier community.